Parents’ Perceptions of Their Children’s Experiences With Distance Learning During the COVID-19 Pandemic - Hamaidi, Diala A.; Arouri, Yousef M.; Noufal, Rana K.; Aldrou, Islam T. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2021)
This study aimed to investigate the perceptions of primary and secondary students’ parents in Jordan toward the distance learning process implemented in light of the coronavirus disease (COVID-19) pandemic. To achieve the study objectives, the researchers used the descriptive survey method to collect and analyze data and interpret the results. After developing the study instrument (questionnaire) and ensuring its validity and reliability, it was distributed to a selected sample, consisting of 470 parents, by random cluster method during the second semester of the 2019–2020 academic year. The study results show that primary and secondary students’ parents were moderately satisfied with the distance learning process implemented in light of the COVID-19 pandemic. In addition, the results reveal statistically significant differences in the parents’ perceptions attributed to the variables of the child’s grade, in favor of grades 5–7; teacher’s gender, in favor of female teachers; and school type, in favor of private schools.